Modification of Variable Returns to Scale Stochastic Data Envelopment Analysis (DEA) Models - Forghani, Seyed Davood (Doğu Akdeniz Üniversitesi, 2021)
Data Envelopment Analysis (DEA) was introduced under the name of a deterministic model assuming all the deviations from the estimated production frontier were one sided indicating technical inefficiency. Biased estimations of inefficiency and production are provided by the model when deviations do not originate only from inefficiency but also from measurement errors. In 1988, Banker developed Data Envelopment Analysis as a stochastic model to reflect inefficiency and statistical noise simultaneously. However, from deterministic to stochastic, the problem with weak efficient frontiers and related biased results stayed the same. This dissertation proposes a modification over Banker’s stochastic DEA (SDEA) model by applying a limitation on the coefficients of inputs in the original model in order to change weak efficient hyperplane(s) while keeps general assumptions behind production function unaffected. This can change the production possibility set (PPS) while the frontier has the potential to give a better representation of the true production frontier. Comparing the results from the stochastic model and suggested modified model shows that the achieved model is providing a new benchmark for relative efficiency evaluation and production frontier estimation. Keywords: Data Envelopment Analysis (DEA), Stochastic Data Envelopment Analysis (SDEA), Modified Model, Weak Efficient Frontier.

ÖZ: Veri Zarflama Analizi (VZA), tahmin edilen üretim sınırından tüm sapmaların teknik verimsizliği gösteren tek taraflı olduğu varsayılarak deterministik bir model adı altında tanıtıldı. Sapmaların yalnızca verimsizlikten değil aynı zamanda ölçüm hatalarından da kaynaklandığında, model tarafından sapmaların verimsizlik ve üretim tahminleri sağlanır. 1988'de Banker, verimsizliği ve istatistiksel gürültüyü eş zamanlı yansıtmak için stokastik bir model olarak Veri Zarflama Analizini geliştirdi. Bununla birlikte, deterministikten stokastiklere Zayıf verimli sınırlar ve ilgili önyargılı sonuçlar ile ilgili sorun aynı kaldı. Bu tez, Banker'in stokastik DEA (SDEA) modeli üzerinde, zayıf etkin hiper düzlem (ler) i değiştirmek için orijinal modeldeki girdi katsayılarına bir sınırlama uygulayarak, üretim fonksiyonunun arkasındaki genel varsayımları etkilenmeden koruyarak bir değişiklik önermektedir. Bu, üretim olasılık kümesini (PPS) değiştirebilirken, sınır, gerçek üretim sınırının daha iyi bir temsilini verme potansiyeline sahiptir. Stokastik model ve önerilen modifiye modelden elde edilen sonuçların karşılaştırılması, elde edilen modelin göreceli verimlilik değerlendirmesi ve üretim sınırı tahmini için yeni bir kriter sağladığını göstermektedir. Anahtar Kelimeler: Veri Zarflama Analizi (VZA), Stokastik Veri Zarflama Analizi (SDEA), Değiştirilmiş Model, Zayıf Verimli sınır.
Master of Science in Industrial Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Industrial Engineering, 2021. Supervisor: Assist. Prof. Dr. Sahand Daneshvar.
Keywords: Data envelopment analysis; Operations research; Operations research-management decision making; Data Envelopment Analysis (DEA); Stochastic Data Envelopment Analysis (SDEA); Modified Model; Weak Efficient Frontier